THE IMPACT OF FEDERAL MORTGAGE INSURANCE PROGRAMS ON ANN ARBOR'S HOME MORTGAGE MARKET, 1956 - Mao, James C. T. (Journal of Finance, 1958)
Lending institutions usually operate in a set pattern with respect to FHA and VA lending. That is, life insurance companies and commercial banks are stronger supporters of federal housing finance programs than savings and loan associations. Therefore, the impact of FHA and VA programs on specific markets is predictable. That is, in those markets where savings and loan associations are the predominant lenders the proportion of insured lending will be lower than in areas where life insurance companies and/or commercial banks predominate. The object of this note is to test the applicability of these conclusions to the city of Ann Arbor, Michigan, a non-metropolitan mortgage market. For the purpose of this note, “market structure” is defined in terms of the percentage distribution of home mortgage recordings among the various types of lenders.22 Gillies and Curtis defined market structure in terms of the proportion of outstanding mortgages held by each type of lender (ibid., p. 364). Since in the Ann Arbor mortgage market the volume of assignments has been small relative to total recordings, the two definitions of market structure are roughly interchangeable for operational purposes. Thus two markets would be “structurally” identical if each type of lender records the same proportions of mortgages in both markets. Under this definition, it is clear from Table 1 that in 1956 the structure of the Ann Arbor mortgage market differed in a number of ways from that of the national market as a whole. With the exception of mutual savings banks, all types of institutional lenders operating in the national mortgage market were repre-sented in the 1956 Ann Arbor market. About 38 per cent of the value of Ann Arbor's home mortgages was furnished by three savings and loan associations—the most important single source of funds. On a national basis, savings associations accounted for 35 per cent of home mortgage recordings. Next in importance to these mutual organizations were four commercial banks, which as a group recorded close to 24 per cent of Ann Arbor's home mortgages. The corresponding figure for commercial banks in the national market was 20 per cent. Life insurance companies, which recorded about 7 per cent of home mortgages on a national basis, were twice as important in the Ann Arbor market. As a group, they underwrote approximately $2.6 million of home mortgages, or 14 per cent of the Ann Arbor 1956 total. Because of the relative abundance of long-term funds from local and national institutions, individuals have been insignificant as a source of mortgage money in Ann Arbor. In 1956, only 3 per cent of the value of home loans on properties within the city were supplied by individuals. The individuals' corresponding share in the national market was 13 per cent. “Other” lenders, who accounted for the remaining 21 per cent of 1956 home mortgage recordings in Ann Arbor, included one trust company, one educational institution, and several mortgage and realty companies. So far, we have described the structural disparities between the Ann Arbor and the national mortgage markets. The question is, with what degree of accuracy can these disparities be utilized to forecast differences in the use of government mortgage insurance programs in the two markets? We know that life insurance companies and commercial banks are strong national supporters of FHA and VA programs; we have seen the greater combined importance of these groups in the Ann Arbor market. Can one predict, on the basis of these points, that the proportion of insured lending would be higher in Ann Arbor, and that of conventional lending accordingly lower, than the national average? Table 2 shows that in 1956 the ratio of conventional lending to total lending in Ann Arbor was actually 73 per cent, 4 percentage points higher than the corresponding national average of 69 per cent. What we have here is apparently a local exception to the general tendency described by the Gillies and Curtis' hypothesis. How can we account for this exception? A closer examination of Table 2 reveals two important circumstances. First, commercial bank activities with respect to conventional lending in Ann Arbor were quite a bit above the national average. While 66 per cent of the total volume of home mortgages recorded by all commercial banks in the United States were of the conventional type, the corresponding figure for Ann Arbor was 77 per cent. Second, “other lenders”-not an unimportant market force-were significantly heavier conventional lenders in Ann Arbor as compared with the national pattern. Thus, while only 25 per cent of the total volume recorded by “other lenders” in the United States was of the conventional type, the comparable figure for Ann Arbor was 76 per cent.33 According to detailed statistics, the predominance of a local educational institution (which restricts itself to conventional lending only) over trust, mortgage, and realty companies was largely responsible for the unusually heavy conventional lending on the part of Ann Arbor's “other lenders.” These two factors combined were apparently more than enough to offset the unusually low conventional lending by life insurance companies in Ann Arbor and to raise the city's ratio of conventional lending to total lending above the national average. The fact that conventional lending in Ann Arbor was proportionately higher than the national average should not lead one to conclude that Ann Arborites were not getting their share of FHA financing. As can be seen from Table 2, 18 per cent of Ann Arbor's 1956 home mortgage recordings were FHA-insured, whereas the corresponding figure for the nation as a whole was only 10 per cent. However, VA financing was considerably more scarce in Ann Arbor. Only 9 per cent of the city's home mortgage recordings in 1956 were VA-guaranteed, whereas the corresponding national figure was as high as 22 per cent. What has caused this peculiar difference in the relative impacts of FHA and VA programs? Perhaps the most important single explanation of the relatively small volume of VA financing in Ann Arbor can be traced to the VA's own appraisal policy. Under the law on VA financing, a home loan is insurable only if the purchase price paid by the veteran for the property does not exceed the “reasonable value” of the property as determined by VA appraisers. However, VA appraisers operating in the Ann Arbor area have been overconservative in their determination of “reasonable value”-overconservative, that is, in relation to Ann Arbor's high construction costs and in relation to what the home buyers are willing and capable of paying. On the other hand, the FHA and conventional lenders have been more realistic about local conditions and are not concerned with setting legal upper limits on purchase prices. As a result of all this, sellers frequently find it more profitable to deal with home buyers who do not need VA financing. This disinclination toward VA financing on the part of sellers is responsible to a considerable degree for the different impacts of FHA and VA programs on the local market.44 This paragraph is based on personal interviews with builders, real estate brokers, and mortgage lending officers operating in the Ann Arbor area. Finally, it should be added that the willingness of Ann Arbor home buyers to pay prices higher than are considered “reasonable” by VA appraisers and their ability to meet the higher down payments under FHA and conventional financing partly reflect their above-average income and wealth positions.55 In 1956, Ann Arbor “households” (defined here as an occupied dwelling unit) had an average disposable income of $10,856, almost twice as high as the corresponding national average of $5,720 (see Standard Rate and Data Service, Inc., Spot Television Rates and Data, XXXIX [May, 1957], 27, 260). In a recent article, Gillies and Curtis advanced the hypothesis that the extent of government-insured mortgage lending in various areas could be predicted on the basis of the structure of local mortgage markets. Their argument was based on the primary assumption that lenders operating in local markets exhibit a clearly delineated set of actions or attitudes with respect to FHA or VA lending. This paper has shown that in 1956, at least, the market structure did not provide us with an accurate basis for predicting the impact of FHA and VA programs on the Ann Arbor market. This is due to the fact that major types of lenders there deviated significantly from their respective national patterns regarding the extent of conventional versus insured lending. The foregoing analysis also suggests that factors other than market structure could be significant in determining the impact of federal housing finance programs on specific markets. Other factors which may have been operative in the 1956 Ann Arbor market include the lending policies of local institutions; the income and wealth positions of home buyers; the level of local construction costs; and the appraisal policy of the VA. It seems clear, therefore, that what the predictability hypothesis of Gillies and Curtis describes is a general tendency—a tendency which is subject to local exceptions such as those which occurred in the Ann Arbor market.